Lateral and Frontal Cephalometric Measurements in a Cohort With Saethre-Chotzen Syndrome. (July 2021) - Rizell, Sara; Karlsson, Peter; Ransjö, Maria; Westerlund, Anna; Yehia, Zakaria; Kölby, Lars
Objective: Descriptions of the craniofacial morphology in Saethre-Chotzen syndrome (SCS) are primarily based on case reports or visual assessments of affected families. The aim of this study was to compare cephalometric measurements of the craniofacial skeleton in a cohort of individuals with SCS and age- and sex-matched individuals without craniofacial anomalies. Design: Retrospective case series. Patients: Eight girls and 4 boys with SCS (age range, 7.0-19.2 years). Methods: Cephalometric measurements were performed using lateral and frontal cephalograms. Results: Most of the individuals with Saethre-Chotzen syndrome exhibited lower values for SNA, SNB, s-n and s-ar, while their NSL/NL, NSL/ML, NL/ML, and n-s-ba values were higher than the respective mean reference values for healthy individuals. In comparison with age- and sex-matched individuals without craniofacial anomalies, the individuals with SCS showed higher values for the maxillary and mandibular angular measurements, as well as for the menton midline angle. Conclusions: This sample of 12 unrelated individuals with SCS is the largest collected to date for cephalometric measurements. We found that the syndrome is associated with bimaxillary retrognathism, posterior maxillary and mandibular inclination, neutral sagittal relation as well as a tendency toward an open vertical skeletal relation, a short and flattened skull base, and facial asymmetry, as compared to individuals without the syndrome.